(R)-(3-Carboxy-2-hydroxypropyl)trimethylazanium chloride - Ng, Seik Weng (International Union of Crystallography, 2012)
In the title salt (common name l-carnitine hydrochloride), C(7)H(16)NO(3) (+)·Cl(−), the organic cation features a carboxylic part (–CO(2)H) having unambigous single- and double-bonds [1.336 (2), 1.211 (2) Å]. There is a large N—C—C bond angle [115.9 (1)°] for the C atom connected to the bulky trimethylamino substituent. In the crystal, the acid H atom forms a hydrogen bond to the chloride anion, whereas the hydroxyl H atom forms a longer hydrogen bond to the anion, generating a helical chain running along [001].